Detection of human bocavirus in nasopharyngeal aspirates versus in broncho-alveolar lavage fluids in children with lower respiratory tract infections - Li, Ling; Zhu, Tian; Chen, Zheng-Rong; Yan, Yong-Dong; He, Li-Ping; Xu, Hong-Mei; Shao, Xue-Jun; Yin, Fang; Ji, Wei (Journal of medical virology, 2016)
To compare the presence of human bocavirus (HBoV) in nasopharyngeal aspirates (NPA) versus broncho‐alveolar lavage fluids (BAL) in children with lower respiratory tract infections (LRTIs), as revealed by real‐time PCR, in order to confirm the diagnostic validity of NPA samples. A retrospective 5‐year study was performed from 2009 to 2014 in 1,194 patients under the age of 17 years (mean age of 3 years) that were diagnosed with LRTIs and from whom both NPA and BAL were obtained. Clinical and demographic data were recorded, and NPA and BAL samples were analyzed for HBoV‐positivity by real‐time PCR. Of the 1,194 patients enrolled, 65 (5.4%) patients had HBoV detected from NPA, and 61 (5.1%) had HBoV detected from BAL. For HBoV, there was a significant association between the NPA and BAL samples (P < 0.001), but the diagnostic validity was relatively low (kappa = 0.414). When real‐time PCR‐positivity for HBoV in BAL was used as a reference for diagnosis, NPA had a good specificity and better positive predictive validity in male patients or those younger than 3 years of age. NPA has a similar yield and a good specificity for diagnosis of LRTIs with HBoV compared to BAL. The best diagnostic validity for NPA was detected in male patients or those younger than 3 years old. J. Med. Virol. 88:211–215, 2016. © 2015 Wiley Periodicals, Inc.